The influence of combined oral contraceptive pills on carbohydrate metabolism in healthy women and in women with PCOS - a systemic review - Katarzyna Wicha; Rafał Wierciszewki; Aleksandra Pokarowska; Anna Hawryluk; Beata Pająk (Kazimierz Wielki University, 2022)
Introduction: Combined oral contraceptives (COCs) are a commonly used contraceptive method. They are used as one of the method therapy in women with PCOS. Outcomes from previous studies about the influence of the COCs on carbohydrate metabolism are diverse. Purpose: To assess the influence of combined oral contraceptives on parameters of carbohydrate metabolism in healthy women and in women with PCOS. Review methods: We conducted a systemic review according to PRISMA protocol. Databases as Pubmed, Scopus, Web of Science were screened systematically.The inclusion criteria were:a study published in 2016-2021, which contains information about the change of carbohydrate parameters as: fasting insulin, fasting glucose levels;HOMA-IR;insulin, glucose levels etc.The participants were healthy/PCOS women. Studies conducted on animals were excluded. The final number of studies enrolled in this study is 15. Abbreviated description of the state of knowledge: There are studies in which negative influences of the COCs on carbohydrate metabolism are proved. Nevertheless, many of these studies were conducted years ago.COCs, when they were introduced in 1960s, contained different compounds and amounts of hormones. Over the years a successive decrease in estrogen dose has occurred . Also progestogens have been developed in order to minimize the androgenic effects.Results of studies conducted nowadays are ambiguous. Summary: A significant impairment of carbohydrate metabolism in short period of time was not detected in healthy women. In women with PCOS the results depended on the type of COCs used.